Evaluation of serum hsa_tsr014055 as a potential biomarker for diagnosis and prognosis of hepatocellular carcinoma - Jing Xu; Bairong Chen; Jing Qi; Jinran Wu; Wei Feng; Kangfeng Jin; Hongyi Bao; Lin Chen; Feng Wang (Annals of Medicine, 2025)
Background Mounting evidence has shown that tRNA-derived small RNAs (tsRNAs) play critical roles in the progression of tumors, including hepatocellular carcinoma (HCC). Nevertheless, the clinical values of serum tsRNAs for HCC are still largely unknown.Methods Serum samples were procured from 153 HCC patients, 93 hepatitis cases, and 89 healthy donors from the Affiliated Hospital of Nantong University. A series of analyses, including qRT-PCR, receiver operating characteristic (ROC) curve, and Kaplan-Meier analysis, were performed to investigate the potential performance of serum tsRNA-Val-5-0035, also known as hsa_tsr014055, for HCC clinical practice.Results Methodological evaluation showed that qRT-PCR detection of serum hsa_tsr014055 had better stability, repeatability, and primer specificity. Moreover, serum hsa_tsr014055 was significantly higher in HCC patients than in hepatitis cases and healthy donors. Dynamic monitoring disclosed that it was dropped in HCC patients who had undergone surgery. Besides, it was positively correlated with TNM stage, differentiation grade, and microvascular invasion, as well as the prognosis of HCC patients. Additionally, serum hsa_tsr014055 had potential diagnostic value for HCC. Importantly, when it was combined with alpha-fetoprotein (AFP) and des-γ-carboxyprothrombin (DCP), the diagnostic efficacy was obviously improved. Also, bioinformatic prediction demonstrated that hsa_tsr014055 had 717 downstream targets, which were enriched in Hedgehog and cAMP signaling pathways.Conclusion Serum hsa_tsr014055 may be a promising biomarker in the diagnosis, evaluation of therapeutic effects, and assessment of HCC prognosis. Especially when serum hsa_tsr014055 was combined with AFP and DCP, the diagnostic efficacy for HCC would be enhanced.